Phenomenology for primary care researchers - Robert Mash; Febisola Ajudua; Sebaka Malope; Doreen Kaura (African Journal of Primary Health Care & Family Medicine)
Primary care researchers often turn to qualitative methodologies to explore people’s perspectives and experiences. Phenomenology is appropriate when the focus is on lived experiences, rather than ideas, beliefs, opinions or perceptions. Phenomenology has its roots in German philosophy and the social sciences, and doctoral students as well as researchers in the health sciences may struggle to understand the paradigm and apply it practically. This article attempts to make sense of the paradigm and two of its key threads, namely descriptive and interpretive phenomenology. The key principles of both approaches and the practical methodological steps are outlined. In addition, examples are given, and the two approaches are compared. Finally, the article discusses trustworthiness and quality criteria in phenomenology.